Deciphering the Origins of P1-Induced Power Losses in Cu(Inx, Ga1–x)Se2 (CIGS) Modules Through Hyperspectral Luminescence. (December 2020) - Ramírez Quiroz, César Omar; Dion-Bertrand, Laura-Isabelle; Brabec, Christoph J.; Müller, Joachim; Orgassa, Kay
Abstract: In this report, we show that hyperspectral high-resolution photoluminescence mapping is a powerful tool for the selection and optimization of the laser ablation processes used for the patterning interconnections of subcells on Cu(In x, Ga1− x )Se2 (CIGS) modules. In this way, we show that in-depth monitoring of material degradation in the vicinity of the ablation region and the identification of the underlying mechanisms can be accomplished. Specifically, by analyzing the standard P1 patterning line ablated before the CIGS deposition, we reveal an anomalous emission-quenching effect that follows the edge of the molybdenum groove underneath. We further rationalize the origins of this effect by comparing the topography of the P1 edge through a scanning electron microscope (SEM) cross-section, where a reduction of the photoemission cannot be explained by a thickness variation. We also investigate the laser-induced damage on P1 patterning lines performed after the deposition of CIGS. We then document, for the first time, the existence of a short-range damaged area, which is independent of the application of an optical aperture on the laser path. Our findings pave the way for a better understanding of P1-induced power losses and introduce new insights into the improvement of current strategies for industry-relevant module interconnection schemes.